Chorioretinitis with retinal ablation complications in patients with cytomegalovirus infections and high myopia: a case report - Thedius Watu; I Gusti Made Ayu Juliari; I Made Agus Kusumadjaja; Ida Ayu Ari Pramita (Intisari Sains Medis, 2021)
Background: Chorioretinitis is uveitis that causes choroidal and retinal inflammation. Chorioretinitis in general due to cytomegalovirus (CMV) infection has been recognized as a major cause of congenital virus infections. A common complication in patients with uveitis is retinal detachment. In addition, high myopia can also cause retinal detachment.Case Illustration: We reported a 33-year-old male patient who came with chief complaints of a sudden blurred left eye the couple of weeks before admission. The patient had a history of high myopia -5D in both eyes and was HIV positive. One week before the complaint, patient underwent laser therapy because of retinal detachment and was also given Neomicin and Potassium Iodide eye drops. Patients presented with vision 1/60. In funduscopy examination, we found vasculitis, retinal detachment, bleeding and exudate. The patient was then diagnosed with OS Rhegmatogenous Retinal Detachment (RRD) caused by CMV chorioretinitis and high myopia ODS. The patient was treated with valganciclovir 1x900mg, methylprednisolone 2x32mg, prednisone eye drops 6x1 OD and underwent pars plana vitrectomy (VPP). The patient had complicated cataracts, therefore phacoemulsification, evacuation and reinjection of silicon oil and endolaser were performed. Unfortunately, the results obtained are not optimal where the patient's vision becomes the patient's no light perception (NLP).Discussion: Retinal detachment is a frequent complication in patients with CMV chorioretinitis. The main therapy is HAART, anti-CMV and operative management. This therapy regimen is proven to improve overall patients’ prognosis.Conclusion: Early diagnosis and appropriate treatment have a very important role in determining the prognosis of patients with CMV chorioretinitis.